Phasing out and in: System transition through disassociation in the German energy transition – The case of light and coal. (October 2021) - David, Martin; Schulte-Römer, Nona
Highlights: A science and technology studies (STS) perspective on discontinuation as a form of transition. Disassociation as a process of ending socio-material relationships. Broader picture to analyse social and material relation in discontinuations. Broader societal perspective on phase-out policies in the fields of coal and lignite. Abstract: In this paper, we focus on and compare policies for phasing-out coal and lignite energy production and light bulbs as part of regime-level climate change mitigation measures. Our approach broadens the transition focus on discontinuation policies by adding a relational STS perspective. Our goal is to understand how the relationships that constitute sociotechnical regimes are deliberately brought to an end. In order to understand this "dissociation", we explore how policymakers instigate phase-out by engaging technology users and producers to loosen their entanglements in existing socio-material networks and eventually end their established sociotechnical relations. In two case studies we show how dissociation was achieved through 1) translating the German coal and lignite phase-out into a regional development challenge and 2) translating a well-established business with highly standardised and cosy incandescent lighting into a fast-changing lead market for energy-efficient LED technology.